The Influence of Self-Efficacy, Vocational Training, and Career Guidance Towards Work-Readiness among Twelfth-Grade Vocational School Students Majoring in Accounting and Finance Institution in Bekasi City - Ramadhan, Suci; Sumiati, Ati; Zulaihati, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the influence of self-efficacy, vocational training, and career guidance on work-readiness among twelfth-grade vocational school students majoring in accounting and finance institution in Bekasi City. This study uses a quantitative method with a questionnaire instrument. The population of this study was twelfth-grade vocational school students majoring in accounting and finance institution in Bekasi City with an affordable population of 313 students. The results of this study show that (1) self-efficacy has a positive and significant effect on work-readiness, (2) vocational training has a positive and significant effect on work-readiness, (3) career guidance has a positive and significant effect on work-readiness, and (4) self-efficacy, vocational training, and career guidance simultaneously have a significant effect on work-readiness.